Direct tracheobronchopexy via left lateral thoracotomy for severe tracheobronchomalacia. (December 2017) - Propst, Evan J.; Zawawi, Faisal; Kirsch, Roxanne E.; Honjo, Osami
Abstract: An infant with pulmonary atresia/ventricular septal defect/major aortopulmonary collateral arteries underwent unifocalization, ventriculoseptal defect closure and placement of a right ventricle to pulmonary artery conduit via median sternotomy. Aortopexy and pulmonary arteriopexy via redo sternotomy were insufficient to allow weaning of continuous positive airway pressure and he required direct tracheobronchopexy via left lateral thoracotomy to alleviate posterior trachealis intrusion along the length of the trachea and left main bronchus. He also underwent laryngotracheoplasty with placement of a posterior costal cartilage graft for bilateral vocal cord paralysis. The patient was weaned from positive pressure and discharged in stable condition.